Sensing properties of palladium-gate MOS (Pd-MOS) hydrogen sensor-based on plasma grown silicon dioxide - Dwivedi D.; Dwivedi R.; Srivastava S.K. (My University, 2025)
This paper deals with the performance of a palladium-gate MOS hydrogen sensor studied by conductance method. Structure of the device was fabricated on a n-type 〈100〉 silicon wafer having resistivity of 1-6 Ω cm using plasma technology. Sensitivity and response-recovery time of the fabricated sensor have been studied for different concentration (1480-11 840 ppm) of hydrogen with varying signal frequency (500 Hz, 10 and 100 kHz) at room temperature. Hydrogen-induced interface-trapped density (Nit) has been also evaluated as a function of gas concentration using a bias scan conductance method. Obtained results show that device performance is improved (i.e., high sensitivity and low response recovery time) and further it has been concluded that implementation of plasma technology (i.e., dry plasma cleaning of Si surface and in-situ RF anodization of Silicon in oxygen plasma near room temperature) may be a future step towards development of MOS-based sensors and integrated arrays with improved performance at room temperature.